Nilai Moral dalam Lirik Lagu “Untuk Perempuan yang Sedang dalam Pelukan” Karya Payung Teduh (Sebuah Kajian Sosiologi Sastra) - Annisa Putri Ramadhani; Dwi Wahyu Candra Dewi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research aims to examine the moral values ​​contained in the lyrics of the song "For Women Who Are in a Hug" by Payung Teduh using a literary sociology approach. This song was chosen because the lyrics are full of meaning and describe the deep emotional relationship between the male and female characters. Through qualitative analysis, it was found that this song contains the values ​​of affection and sincere love, emotional honesty, simplicity, gratitude, and respect for women. These values ​​not only reflect healthy personal relationships, but also reflect the social conditions of modern society which is experiencing a crisis of emotional closeness due to the dominance of materialistic lifestyles. The results of this study show that song lyrics as part of popular literary works can be an effective medium in conveying moral and social messages in a subtle but profound manner.